Integrating Local Wisdom and Creative Economy through an Online Collaborative Curriculum in Rural English Education - Butarbutar, Ranta; Florensi Sauhenda, Angla; Indriyani, Novi; Agustina Wakerkwa, Dian (Innovations in Pedagogy and Technology, 2025)
Online Collaborative Curriculum (OCC) is an innovative pedagogical model that integrates local wisdom and the creative economy into English language education in rural areas. This study explored teachers' perceptions and the impact of OCC in business and economics courses. Data were collected through interviews, observations, focus group discussions, and document analysis. Results indicated that teachers had positive perceptions of OCC. The learning scheme utilized Zoom for online presentations, WhatsApp Groups for written discussions, recorded videos on YouTube, Facebook, and TikTok for assignment submission, and Google Docs and email as collaborative evaluation tools. OCC was proven to improve students' language skills while providing economic, social, and cultural insights. The researchers concluded that integrating local wisdom and the creative economy in OCC is an innovative approach to ESP teaching for BEC courses. This curriculum allows teachers to connect local potential with international business competencies. The flexibility and cost-efficiency of OCC positively impacted language acquisition, economic knowledge, cultural preservation, and social interaction. However, the involvement of only one ESP teacher is a limitation of this study. Further research involving more ESP teachers and cross-regional case studies is recommended to broaden generalizability. Comparative studies and quantitative validation are also recommended to strengthen the methodology and impact of OCC going forward.